Somatic distress, mental health and psychological resilience among cancer patients during the Covid-19 pandemic - Sağaltıcı, Eser; Sönmez, Özcan; Karcı, Ebru; Şahin, Şengül Kocamer; Erturk, Arzu (Universitas Negeri Padang, 2021)
We aimed to investigate the somatic distress and psychological symptoms levels of cancer patients, and analyze the influencing factors on somatic distress during COVID-19 pandemic. This cross-sectional study included 216 eligible cancer patients. The Patient Health Questionnaire-15, Post-Traumatic Stress Disorder (PTSD) Checklist for DSM-5, The Depression, Anxiety and Stress Scale-21, the Brief Resilience Scale, the Stressful Life Events List due to Pandemic were administered to the participants. The moderate to severe somatic distress rate was % 38 and probable PTSD rate was 20.4%. Depression, anxiety and stress symptoms were 36.1%, 49.1% and 45.4%, respectively, from mild to extremely severe. There were substantial association between somatic symptoms severity and high PTSD, anxiety, depression, and stress symptoms levels. Low education, high anxiety levels, high experience stressful life events, and low psychological resilience predicted high somatic distress. This study demonstrates the high risk of somatic distress, PTSD, depression, anxiety and stress in patients with cancer during the pandemic. In addition, somatic distress may indicate high levels of psychological symptoms, high experience stressful life events, and low psychological resilience. It underscores the need to assess psychological status during the pandemic, especially those with high level somatic symptoms.